A Mathematical Model for Hyperbolic Space-fractional Bioheat Transfer during Thermal Therapy - Kumar P.; Kumar D.; Rai K.N. (My University, 2025)
In this paper, we have developed a hyperbolic space-fractional bioheat transfer model based on the single-phase-lagging constitutive relation. The numerical solution of the present problem has been done using fractional backward finite difference scheme and Legendre wavelet Galerkin approach. The effect of fractional parabolic and hyperbolic bioheat transfer model on temperature profile within living biological tissues has been studied and compared with their respective standard cases. Numerical results are presented graphically in both standard and anomalous case for different values of parameters. © 2015 The Authors.